Public Health and Early Childhood Education: An Analysis of Chinese Pre-service Teachers’ Reflections During the COVID-19 Pandemic - Lo, Wing Yee (Frontiers in Education, 2021)
The purpose of this study was to investigate Chinese pre-service kindergarten teachers’ beliefs and behaviors inherent to a public health perspective in the time of coronavirus disease (COVID-19) pandemic. The study intended to deepen our understanding of the contextual factors that may influence their future implementation of public health education in early childhood settings. Forty-five participants were recruited from an early childhood teacher education program, with the majority (n = 41) reporting that they lived through the strict restrictions in different regions of China during the initial COVID-19 outbreak. Data were collected via a reflective writing task from an online course. The results indicated an increasing awareness of public health among the participants due to the COVID-19 crisis. Their personal hygiene behaviors included personal protection, cleaning, disinfection, physical distancing, avoidance, and ventilation. The pandemic also changed pre-service teachers’ beliefs about the importance of public health education. Although the participants seemed to have positive attitudes toward public health education, evidence of their limitations of knowledge and skills was further exposed in their ideas for teaching health-related topics. When there is a need to strengthen public health education in the ongoing fight against COVID-19, this paper calls for a refocus in pre-service teacher education to improve public health outcomes for young children.